Postnatal Education Package for Breastfeeding Motivation And Self Efficacy Postpartum Mother's Early Stage - Made Ririn Sri Wulandari; Ni Made Ari Sukmandari; Pande Putu Indah Purnamayanthi (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The postpartum period is a phase of adaptation in accepting a new role as a mother. During this period experienced, several changes occurred in mothers and their partners and their families, especially in the early week after giving birth. As a form of maternal support, which is an essential key to the health of the mother and baby, a supportive education structure is crucial to give. The Family-Centered Maternity Care (FCMC) approach can be a choice for mothers to adapt to role changes, especially for maternal beliefs in caring for infants and motivations to give breast milk. Objective: This study aimed to determine the effect of PEP (Postnatal Education Package) on self-efficacy and breastfeeding motivation among mothers during the early postpartum period. Method: This study uses pre-experimental research methods with one group pretest-posttest. Result: The results showed increased breastfeeding motivation and self-efficacy among mothers after receiving the intervention (p-value of <0.0001). Conclusion: Education supportive structured with the FCMC approach can concern health workers improve further education programs to help increase competent mothering during the postpartum period